Notes to Philosophy 167: Class 5 -- Other Developments in Astronomy from 1609 to 1642 -- Part 15. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: The "Copernican Revolution" -- 100 Years -- Major Open Questions: Evidential Problems -- The Changing Conception of the Science -- Select Sources; Generally corresponds to the video segment: Class 5, Part 15.